Foot and ankle muscle strength in people with gout: A two-arm cross-sectional study. (February 2016) - Stewart, Sarah; Mawston, Grant; Davidtz, Lisa; Dalbeth, Nicola; Vandal, Alain C.; Carroll, Matthew; Morpeth, Trish; Otter, Simon; Rome, Keith
Abstract: Background: Foot and ankle structures are the most commonly affected in people with gout. However, the effect of gout on foot and ankle muscle strength is not well understood. The primary aim of this study was to determine whether differences exist in foot and ankle muscle strength for plantarflexion, dorsiflexion, inversion and eversion between people with gout and age- and sex-matched controls. The secondary aim was to determine whether foot and ankle muscle strength was correlated with foot pain and disability. Methods: Peak isokinetic concentric muscle torque was measured for ankle plantarflexion, dorsiflexion, eversion and inversion in 20 participants with gout and 20 matched controls at two testing velocities (30°/s and 120°/s) using a Biodex dynamometer. Foot pain and disability was measured using the Manchester Foot Pain and Disability Index (MFPDI). Findings: Participants with gout demonstrated reduced muscle strength at both the 30°/s and 120°/s testing velocities for plantarflexion, inversion and eversion ( P < 0.05). People with gout also displayed a reduced plantarflexion-to-dorsiflexion strength ratio at both 30°/s and 120°/s ( P < 0.05). Foot pain and disability was higher in people with gout ( P < 0.0001) and MFPDI scores were inversely correlated with plantarflexion and inversion muscle strength at the 30°/s testing velocity, and plantarflexion, inversion and eversion muscle strength at the 120°/s testing velocity (all P < 0.05). Interpretation: People with gout have reduced foot and ankle muscle strength and experience greater foot pain and disability compared to controls. Foot and ankle strength reductions are strongly associated with increased foot pain and disability in people with gout. Highlights: Peak isokinetic muscle torque of the foot and ankle was measured in people with gout. Plantarflexion, inversion and eversion muscle strength is reduced in people with gout. Reduced muscle strength is associated with increased foot pain and disability.